3D printing of biomedical materials and devices - Bandyopadhyay, Amit; Ghosh, Sourabh; Boccaccini, Aldo R.; Bosenaff, Susmita (Journal of Materials Research, 2021)
3D printing, or additive manufacturing, is a transformative technology platform impacting various disciplines, including biomaterials and biomedical devices. We present scientists, engineers, and medical professionals' perspectives about 3D printing of biomaterials and biomedical devices in this special issue. This issue is geared towards understanding the structure–process–property relationships involving different materials in vitro, in vivo, and in silico environments. The focus issue covers polymer, ceramic, glass, metallic and composite biomaterials involving various 3D-printing processes such as fused deposition, powder bed fusion, Bioprinting, directed energy deposition, and binder jetting; addressing research topics including tissue engineering, drug delivery, porous metal implants, bioink development, cell–materials interactions, wear degradation, nano-bio materials, and challenges in point-of-care delivery. Such diversity of research topics is an accurate representation of what is happening in this field globally. This article presents some of the success stories, challenges, and future directions in the 3D printing of biomaterials and devices. Graphic abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2021-11-05
Keywords: 3D printing; Additive manufacturing; Biomaterial; Biomedical